Effect of Clinacanthus nutans Leaf Chloroform Extract on Reducing Nitric Oxide in Fibroblasts - Erdita Hapsari; Rezky Anggraeni; Komariah Komariah; Moehamad Orliando Roeslan (Scientific Dental Journal, 2023)
Background: Clinacanthus nutans or dandang gendis is a plant that can be an effective herbal treatment for inflammation, in addition that the Indonesian people are still looking for alternative treatments. Research shows that the anti-inflammatory properties of C. nutans leaves are effective in reducing inflammation against fibroblasts. Nitric oxide is one of the inflammatory mediators, that release by fibroblast when inflamed. Objective: To observe the effect of C. nutans leaf chloroform extract on reducing nitric oxide in inflamed fibroblasts. Methods: Fibroblasts stimulated with Escherichia coli lipopolysaccharide were treated with chloroform extracts of C. nutans leaves at concentrations of 25, 50, 100, 200 μg/mL for 24 hours, then a nitric oxide inhibition test was performed. Result: The C. nutans leaf extract at a concentration of 200 μg/mL resulted in significantly (p < 0.05) lower nitric oxide production than the negative control. Conclusion: Clinacanthus nutans leaf chloroform extract has the effect of reducing nitric oxide in fibroblasts. This extract has the potential as an anti-inflammatory agent.